Peer-assessment on the students’ performance of interpreting prose text - Titik Ismailia; Nila Susanti (Journal of English in Academic and Professional Communication, 2018)
Peer-assessment is one alternative assessment to grade  peers in group or individuals by commenting on and judging other students work. This kind of evaluation  helps a teacher to have a different view on giving value and comment to the students’ performance. Interpreting is translating spoken discourse orally. There are some types of interpreting from the experts, they are simultaneous interpreting, consecutive interpreting, whispered interpreter, conference interpreting, seminar interpreting, escort interpreting. Some requirements needed like ability to speak clearly, clarity, fluency, eye contact, and self-confidence. Some experts give opinion on evaluating student’s performance on interpreting such as AIIC adopted from Bühler, EMCI, and Schjoldager. From those experts, the writer formulated one form of assessment for student in interpreting class.  Prose text is a kind of expressive text and it needs some requirements to translate like ability to comprehend parts and whole story, idioms, structure, culture, and expressions. This paper  discusses the results of students’ performance on consecutive interpreting prose text with their partner through video. One student gave the score and comment for the other student on the assessment sheet while they were watching video in the classroom. The result shows that there were 1 (1,5%)  student categorized into poor, 14 (21,5%) students categorized into fair, 33 (50,8%) students categorized  into good, and 17 (26,2%) students categorized into very good.   Keywords: Peer-assessment, interpreting prose text, students’performance